Investigação da cintilação ionosférica no Brasil e seus efeitos no posicionamento por GNSS - Mendonça, Marco Aurelio Moraes de [UNESP] (2013)
Several navigation and communication systems rely on electromagnetic waves that pass through the ionosphere at some moment of its working process. It’s known that the Earth’s ionosphere is a dispersive medium and highly dynamic, with seasonal characteristics that last from milliseconds to tens of years. Another important characteristic is the spatial variability of the ionosphere, which gives to this matter different approach opportunities. Among the phenomena that happen in the ionosphere, one of the most important is the ionospheric scintillation. The scintillation is an effect of the ionosphere that most affect spatial activities, specially the GNSS positioning and navigation activities. Knowing that those activities are, sometimes, essential to parts of society, scintillation occurrences may become an issue not only in the academic field, but also monetary and even a security problem. Nowadays, there is an expressive interest of industry and a good acceptance, nationally and internationally, on this subject, making this an open field of research and brainstorming. In this Master Degree thesis, there is a theoretical revision about the effects that triggers the ionospheric scintillation since its origins: the Sun and the Earth’s inner layers. Therefore, it is described here an approach of interpretation and correlation of these indexes with the observed effects in GNSS...